The Causes and Consequences of Flood-induced Temporary Displacement in Southwest Coastal Bangladesh - Tonni, Khairtun Hisan; Begum, Mst. Hosne Ara; Parvin, Rawnaq Ara (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
The main objective of this study was to explore the causes and consequences of flood-induced temporary displacement in southwest coastal Bangladesh. To investigate this, we purposively select one village; Hazrakhali, under the Satkhira district as our study area. This project has been carried out by following a qualitative research approach. Data for this study is collected through in-depth interviews conducted with 20 household heads who were selected using snowball sampling. The findings show that the dominant causes of temporary displacement in that area include economic challenges, the fear of losing their social connections, and a deep attachment to their cultural heritage. This temporary displacement had long-term negative consequences for their livelihoods in terms of poverty, rehabilitation problems, food insecurity, income diversification, hygiene and sanitation troubles, scarcity of edible water, etc. These findings will advocate for policymakers and disaster management bodies to address and mitigate the impacts of flood-affected miseries induced by displacement in the region.